BFKL dynamics at hadron colliders - Ewerz, Carlo (Journal of physics. G, Nuclear and particle physics, 2000)
Hadron colliders can provide important tests of BFKL `small- x ' dynamics. We discuss two examples of such tests, the inclusive dijet jet cross section at large rapidity separation and the number of associated `mini-jets' in Higgs boson production.